Model of Communication Strategy for Public Relations in Private University in Building The Relationship With The Media - Rini Darmastuti; Lina Sinatra Wijaya (The Indonesian Journal of Communication Studies, 2009)
The success of Public Relations work in Private University depends on the public relations strategy in building the relationship with the media. For knowing how effective PR strategy is in building the relationship with the media, A research has been done with 10 respondents ( 10 Private Universities in Central Java ) by using descriptive qualitative approach and direct observation. There are two relationship models that have been found from this research, they are “ Imbalanced Commensalisms Relationship “ ( for PR’s relationship with the media institution ) and “ Harmonious Mutualism Relationship “ ( for PR’s relationship with the Journalist).